Digital Marketing Strategy for Patient Visit Decisions with Brand Awareness as an Intervening Variable at Fatma Eye Hospital - Maulana Ali Syahidin; Hadiah Fitriyah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study investigates the effect of digital marketing on patient visit decisions with brand awareness as an intervening variable at Fatma Eye Hospital. A quantitative explanatory design was employed using purposive sampling with 100 respondens. Data were collected through structured questionnaries and analyzed using SEM-PLS. The result reveal that digital marketing significantly influences both brand awareness and patient visit decisions. Brand awareness also has a significant effect on patient visit decisions and mediates the relationship between digital marketing and patient decisions. These findings confirm the role brand awareness as a cognitive mechanism linking digital marketing to behavioral outcomes. The study provides theoretical and practical implications for optimizing integrated digital marketing strategies to enchance hospital competitiveness and patient acquisition.